Crystal structure of N,N′-dibenzyl-3,3′-dimethoxybenzidine - Im, Hansu (Acta Crystallogr E Crystallogr Commun, 2018)
The title compound, (systematic name: N,N′-dibenzyl-3,3′-dimethoxy-1,1′-biphenyl-4,4′-diamine), C(28)H(28)N(2)O(2), was synthesized by the reduction of a Schiff base prepared via a condensation reaction between o-dianisidine and benzaldehyde under acidic conditions. The molecule lies on a crystallographic inversion centre so that the asymmetric unit contains one half-molecule. The biphenyl moiety compound is essentially planar. Two intramolecular N—H⋯O hydrogen bonds occur. The dihedral angle between the terminal phenyl and phenylene rings of a benzidine unit is 48.68 (6)°. The methylene C atom of the benzyl group is disordered over two sets of sites, with occupancy ratio 0.779 (18):0.221 (18). In the crystal, molecules are connected by hydrogen bonding between o-dianisidine O atoms and H atoms of the terminal benzyl groups, forming a one-dimensional ladder-like structure. In the data from DFT calculations, the central biphenyl showed a twisted conformation.